KORELASI DETERMINAN SOSIAL EKONOMI PETANI DENGAN KECENDERUNGANNYA MERAMBAH HUTAN LlNDUNG D1 TAMAN NASIONAL KERINCI SEBLAT (TNKS) - Purwoko, Agus (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2004)
This research was to analyze the relationship between determinants of socio-economics and farmers' tendency to clear away the forest in Taman Nasional Kerinci Seblat (TNKS). A survey method was carried out at nine villages in the border of TNKS, Lebong Se/atan subdistrict, Rejang Lebong district. The total of respondents were 130 farmers that selected by proportional simple random sampling based on the size of subpopulation from each village. Rank Spearman correlation was used to examine the relationship between determinants of socio-economics and farmers' tendency to clear away the forest in TNKS. The results showed most of farmers tend to dear away the forest in TNKS. The variables of socioeconomics related to farmers' tendency were the size of farmland, the financing offann, and family income.